1993
DOI: 10.1007/bf01967256
|View full text |Cite
|
Sign up to set email alerts
|

Western blot analysis of sera from Lyme borreliosis patients according to the genomic species of theBorrelia strains used as antigens

Abstract: Sera of 52 Lyme borreliosis patients classified according to their clinical features were analysed by Western blot using as antigens Borrelia strains belonging to three recently described genomic species. The antibody response was demonstrated to be homologous within each genospecies. Serum reactivity was studied for each of the type strains Borrelia burgdorferi sensu stricto (strain B31T), Borrelia garinii (strain 20047T) and group VS461. Seven of 15 sera (46.6%) of patients with meningoradiculitis showed pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
102
1
1

Year Published

1995
1995
2010
2010

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(118 citation statements)
references
References 32 publications
14
102
1
1
Order By: Relevance
“…The genetic distances that separate these groups are consistent with data that were obtained by using a different collection of strains and a smaller number of enzyme loci (15). As reported previously, B. burgdorferi sensu stricto, B. garinii, and B. afzelii are preferentially associated with different chronic manifestations of Lyme disease (7,9,47). Briefly, it appears that the first symptom of the disease, erythema chronicum migrans, is associated with all three of these species, whereas arthritis and acrodermatitis chronica atrophicans are caused by B. burgdorferi sensu stricto and B. afzelii, respectively, and neuroborreliosis occurs after infection by B. garinii or B. burgdo$eri sensu stricto.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The genetic distances that separate these groups are consistent with data that were obtained by using a different collection of strains and a smaller number of enzyme loci (15). As reported previously, B. burgdorferi sensu stricto, B. garinii, and B. afzelii are preferentially associated with different chronic manifestations of Lyme disease (7,9,47). Briefly, it appears that the first symptom of the disease, erythema chronicum migrans, is associated with all three of these species, whereas arthritis and acrodermatitis chronica atrophicans are caused by B. burgdorferi sensu stricto and B. afzelii, respectively, and neuroborreliosis occurs after infection by B. garinii or B. burgdo$eri sensu stricto.…”
Section: Discussionsupporting
confidence: 71%
“…Several groups of workers, including our group, have demonstrated that there is an association between these three species and the different chronic manifestations of Lyme disease. B. afzelii and B. gan'nii have been found to be associated with acrodermatitis chronica atrophicans and neuroborreliosis, respectively, and arthritis, which is the predominant late complication of the disease in the United States, has been found to be associated with B. burgdofen' sensu stricto (7,9,47).…”
mentioning
confidence: 99%
“…There are differences in the antigen profile between various species of LB spirochetes that are specifically revealed in the molecular interactions of pathogen with molecular factors (receptors) of tick or host inner environment. Due to the above-mentioned molecular differences significant diversities exist in the LB clinical picture (Assous et al 1993, van Dam et al 1993. Prevalence rates of B. burgdorferi sensu lato in host-seeking Ixodes ricinus ticks in Europe were estimated by Hubálek and Halouzka (1998).…”
Section: Genospecies Of Borrelia Burgdorferi Sensu Latomentioning
confidence: 99%
“…In Europe, at least three genospecies are recognized as human pathogens: B. burgdorferi sensu stricto, B. garinii and B. afzelii (Assous et al 1993, Van Dam et al 1993, Wang et al 1999. Depending on the geographical location, various species of the hard-bodied (ixodid) ticks transmit B. burgdorferi s.l.…”
mentioning
confidence: 99%